Spatial and temporal variability in costs and effectiveness in phosphorus loss mitigation at farm scale: A scenario analysis. (1st September 2019) - Bragina, Lyubov; Micha, Evgenia; Roberts, William M.; O'Connell, Kay; O'Donoghue, Cathal; Ryan, Mary; Daly, Karen
Abstract: Current policy instruments under the EU Water Framework Directive (WFD) to mitigate phosphorus (P) loss require that P use on farms is managed through regulation of farm gate P balances. Regulation at farm scale does not account for spatial variability in nutrient use and soil fertility at field scale, affecting the costs and effectiveness of farm gate measures. This study simulated the implementation of a P loss mitigation measure coupled with improving soil fertility so that farm productivity would not be compromised. The measure was simulated at field scale and the costs and effectiveness assessed at farm scale. Effectiveness was expressed as the time taken for excessive soil P levels to decline to levels that matched off-takes and this varied temporally and spatially within and between farms ranging from 1 to 8 years. Sub-optimum soil fertility was corrected on all fields across both farms, with applications of other soil nutrients and lime to protect productivity. An increase in costs ranging from 1.5 to 116% was predicted in the first two years of the measure on both farms after-which savings of 15–31% were predicted for each subsequent year until the measure was effective in year 9. Despite initial cost increase, there was no statistically significant difference in costs over the time taken for the measure to be effective, when compared to baseline costs. Successful implementation of measures should consider the impact on farm costs and time taken for measures to environmentally effective. Adoption of measures could improve if demonstrating to farmers that costs will not vary significantly from current practice and in time may results in savings if measures are paired with correcting soil fertility and increasing yields. This 'win-win' approach could be used into the future to ensure successful implementation and uptake of measures within the farming community. Highlights: Soil P decline as a source control varied from 1 to 9 years on two farms. Coupling P mitigation with improving fertility to protect yields is cost effective. Effectiveness varied spatially and costs temporally in farm scale simulation. Cost effectiveness of policy measures should be assessed over longer time periods.